A SYSTEMATIC REVIEW OF BESSEL FUNCTION-BASED HEAT TRANSFER MODELING IN SEMI-CYLINDRICAL THERMAL ENERGY STORAGE AND THERMOELECTRIC GENERATORS - Fatmawati, Fatmawati; Akhsan, Hamdi; Hayati, Suci Husnul; Aljuzza, Muhammad Ikhsan; Andriani, Nely; Amalia, Wardah (JOURNAL ONLINE OF PHYSICS, 2026)
Heat transfer modeling in semi-cylindrical systems is crucial in the development of thermal energy storage (TES) and thermoelectric generator (TEG) technologies. This study aims to analyze the integration of Bessel functions and computational methods in thermal conduction modeling, as well as evaluate their effectiveness for thermal system optimization. The method used is Systematic Literature Review (SLR) with literature searches in ScienceDirect, MDPI, SpringerLink, arXiv, and DOAJ (2020–2025), followed by selection based on inclusion-exclusion criteria and thematic synthesis of 21 selected articles. The results show that Fourier–Bessel series-based semi-analytical solutions are capable of representing radial temperature distributions even under asymmetric boundary conditions, while hybrid approaches combining Bessel functions with the Finite Element Method (FEM) or Computational Heat Transfer (CHT) improve prediction accuracy and computational efficiency. Key challenges include sensitivity to material parameters, numerical instability, and high computational costs for nonlinear geometries. Practically, this approach can be utilized by renewable energy researchers and engineers to design semi-cylindrical TES and TEG systems with more uniform temperature distribution, higher storage capacity, and optimal thermoelectric conversion efficiency.